The Relationship Between People Pleaser Behavior and Psychological Well-Being in Generation Z - Fikriyah Futik Ayu; Annisa Warastri (Golden Ratio of Social Science and Education, 2026)
Generation Z in Indonesia faces increasingly complex social pressures, particularly in interpersonal relationships that emphasize acceptance and social harmony. One emerging response to these pressures is people-pleasing behavior, defined as an excessive effort to satisfy others at the expense of one’s own needs. This study aims to examine the relationship between people-pleasing behavior and psychological well-being among Generation Z in the Special Region of Yogyakarta, while highlighting its psychological implications within the Indonesian socio-cultural context. A quantitative correlational design was employed, involving 103 respondents aged 18–25 years. The instruments used were the People Pleaser Scale and the Psychological Well-Being Scale, both of which demonstrated adequate validity and reliability. The results indicated that the majority of respondents exhibited low levels of psychological well-being (87.4%) and high levels of people-pleasing behavior (61.2%). Product moment correlation analysis revealed a very strong negative relationship between people-pleasing behavior and psychological well-being (r = −0.852) with a significance value of 0.000 (p < 0.05). Furthermore, the results of the coefficient of determination test showed an R Square value of 0.726, indicating that the people-pleaser variable contributes 72.6% to psychological well-being among Generation Z in the Special Region of Yogyakarta. These findings contribute novel insight by demonstrating that people-pleasing tendencies among Indonesian Generation Z are not merely adaptive social strategies, but may constitute a significant risk factor for diminished psychological well-being. This study enriches the field of developmental psychology and mental health by emphasizing the importance of strengthening autonomy, self-acceptance, and personal boundaries among Generation Z. Practically, the findings provide a foundation for psychological interventions, counseling services, and self-development programs aimed at enhancing psychological well-being and preventing the adverse effects of people-pleasing behavior among young people in Indonesia.